Lifetime Paid Work and Mental Health Problems among Poor Urban 9-to-13-Year-Old Children in Brazil - Isabel A. Bordin; Ivens H. Pires; Cristiane S. Paula (The Scientific World Journal)
Objective. To verify if emotional/behavioral problems are associated with lifetime paid work in poor urban children, when taking into account other potential correlates. Methods. Cross-sectional study focused on 9-to-13-year-old children (n=212). In a probabilistic sample of clusters of eligible households (women 15–49 years and son/daughter <18 years), one mother-child pair was randomly selected per household (n=813; response rate = 82.4%). CBCL/6-18 identified child emotional/behavioral problems. Potential correlates include child gender and age, socioeconomic status/SES, maternal education, parental working status, and family social isolation, among others. Multivariate analysis examined the relationship between emotional/behavioral problems and lifetime paid work in the presence of significant correlates. Findings. All work activities were non-harmful (e.g., selling fruits, helping parents at their small business, and baby sitting). Children with lower SES and socially isolated were more involved in paid work than less disadvantaged peers. Children ever exposed to paid work were four times more likely to present anxiety/depression symptoms at a clinical level compared to non-exposed children. Multivariate modeling identified three independent correlates: child pure internalizing problems, social isolation, and low SES. Conclusion. There is an association between lifetime exposure to exclusively non-harmful paid work activities and pure internalizing problems even when considering SES variability and family social isolation.